Diagnóstico de la gestión administrativa de la escuela de conducción Marcos Quinto Andrade Zambrano del cantón Chone - Gómez Mejía, María Fernanda (2023)
The present research work consisted of diagnosing the administrative management of the Marcos Quinto Andrade Zambrano Driving School in Chone canton, administrative management has one purpose and is to achieve the proposed objectives with the management of the processes that every manager pursues, but when this does not happen, the problems persist affecting the functionality of the company, it is important to highlight every relationship, communication is an indispensable factor in the daily life of a company, for this reason this research is of utmost vitality and importance, to meet the objective of this research the methodology applied was the observation technique, which allowed us to know firsthand the problems that the staff was going through and how much it had an impact on the work environment. This allowed us to carry out the SWOT analysis, to continue deepening the study. Additionally, when conducting the survey to the officials, convenience sampling was chosen, which is the sample that is chosen according to the convenience of the researcher, the interview was also carried out with the manager of the institution, based on the results in an objective and precise manner. The problem was latent, indisputable and worrying, for this reason it was necessary to propose an improvement plan for the company, which will allow correcting the stages of the processes that are planning, management, organization and control and this in turn would flow with the Personally and positively, a business image is built with effective communication.